OPTIMISASI MAXIMUM POWER POINT TRACKER (MPPT) SISTEM PHOTOVOLTAIC (PV) ALGORITMA PADA PENGISIAN BATERAI KENDARAAN LISTRIK BERBASIS FIREFLY ALGORITMA MODIFIKASI - Dwi Ajiatmo; Imam Robandi (SENTIA 2015, 2015)
This paper presents the electric car today has evolved rapidly in both research table prototype design, aerodynamics, and implementation. One source of energy that is widely used as a source of electrical energy to drive the vehicle was photovoltaic (PV). To obtain maximum performance of PV power required a method of control. PV maximum power is strongly influenced by temperature and solar irradiation value that falls on the surface of the PV. Maximum power point of the PV obtained through adjustment of the duty cycle of the boost converter. Boost converter is used to convert the voltage direct current (DC) low into high DC voltage obtained MPPT. Design Optimization based Firefly modified MPPT able to control the power output of PV systems that are connected to an electric vehicle with a high of efficiency so as to charge the battery optimally. The simulation results in this study showed a high efficiency performance accuracy using the modified algorithm firefly.